Intracholecystic tubular non-mucinous neoplasm (ICTN) of the gallbladder: a clinicopathologically distinct, invasion-resistant entity - ERBARUT SEVEN, İPEK; BAĞCI ÇULÇİ, PELİN (SPRINGER, 2021)
Preinvasive tumor-forming gallbladder neoplasms that are composed of small, non-mucinous tubules with complex architecture remain a poorly characterized group. Here, we evaluated the clinicopathological characteristics of this entity. Twenty-eight examples were analyzed. Tumors were invariably pedunculated polyps with thin stalks, often presented as loosely attached intraluminal nodules, with cauliflower architecture (akin to cholesterol polyps) comprised of compact, back-to-back acinar-like, small tubular units with minimal/no cytoplasm showing variable complexity, creating a picture distinct from the other tubular type dysplasia in the gallbladder. Their limited stroma showed distinctive amorphous amyloid-like hyalinization (39%). While some had round nuclei with single prominent nucleoli, others exhibited slightly more elongated nuclei with washed out chromatin reminiscent of papillary thyroid carcinoma. Squamoid/meningothelial-like morules (71%) and subtle neuroendocrine cell clusters (39%) were frequent. The level of cytoarchitectural atypia qualified as high-grade dysplasia (HGD) in all cases, but none were invasive. The background mucosa showed no dysplasia, but cholesterolosis. The majority (n = 8/12) showed diffuse MUC6 expression and lacked MUC5AC expression. Based on these observations, 635 gallbladder carcinomas were re-analyzed for residual/adjacent lesions with entity-defining characteristics disclosed here, and none could be identified. Preinvasive tubular non-mucinous neoplasm of the gallbladder, which we propose to classify as intracholecystic tubular non-mucinous neoplasm, is a clinicopathologically discrete entity, which tends to occur in uninjured gallbladders and in association with cholesterol polyps. By being tubular, non-mucinous and MUC6-positive, it is akin to intraductal tubulopapillary neoplasms of pancreatobiliary tract, but it is also different in many other aspects. Although their cytoarchitectural complexity warrants an HGD/carcinoma classification, they do not show invasion and their distinct characteristics warrant their separate classification.
Keywords: Gallbladder; Adenoma; Preinvasive neoplasm; Tubular Papillary; Pyloric; INTRADUCTAL TUBULOPAPILLARY NEOPLASMS; PANCREATIC INTRAEPITHELIAL NEOPLASIA; BETA-CATENIN; LOCALIZATION; PATHWAY